Pengaruh Jenis Pengaduk Dan Waktu Fermentasi Pada Pembuatan Bioetanol Dari Sari Nenas Reject - Junuansyah, Muh Wawan; Chairul, Chairul; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is a liquid of fermentation of sugars from carbohydrate source that uses the help of microorganisms. Bioethanol is an energy source with good prospects as a substitute for liquid fuels renewable raw materials, friendly to the environment and the very favorable economic terms. One of the materials that can be used as raw material for bioethanol is pineapple. The fermentation process is influenced by several factors, among which the fermentation time and stirring in a liquid medium. Flow pattern and degree of turbulence is an important aspect which affects the quality of mixing that depends on several factors such as tank geometry, physical properties of fluids and type of impeller. Fermentation time very big influence on the activity of yeast because the longer the fermentation, the more number of increasingly active yeast or yeast to proliferate. The process of fermentation using yeast Sacharomyces cereviceae. Preparation starter made with yeast inoculum process Sacharomyces cereviceae at 10% glucose so that the yeast to multiply. Fermentation takes place in batch, variations in the type of agitator Paddle, pitched Blade Turbine, Turbine Disk and variations in the fermentation time 24, 36, 48, 60 and 72 hours. Stirring speed of 200 rpm and the temperature of fermentation in temperature. Ethanol concentration was analyzed using Alkoholmeter. The optimum fermentation process is shown on the type of agitator pitched Turbine Blade fermentation time of 48 hours with the acquisition of bioethanol concentration of 8.5% (v / v).Keywords : Bioethanol, Reject Pineapple, Saccharomyces Cerevisie, Impeller Type, Flow Pattern